Local Gains from Global Opportunities : Improving Central America's Investment Climate - World Bank (Washington, DC, 2012)
Central America's economic performance in recent years has benefited from improved macroeconomic management, a favorable external environment, as well as rising investor confidence since the region has pursued greater access to global markets, particularly with the signing Dominican Republic, Central American Free Trade Agreement (DR-CAFTA) in 2004. Nonetheless, while important reforms have been made, much remains to be done, and the context of a less favorable global environment underlines the urgent need to improve competitiveness and enhance productivity. An improving investment climate will contribute to both. This chapter discusses the broad economic factors that shape the investment climate in Central America. Section one describes the overall strategic context, highlighted by the opportunities and challenges emerging from the new trade deal. Section two discusses the region's macroeconomic environment, economic growth, sectoral changes, the business cycles with the US, and overall stability. Section three covers trade, financial and remittances flows, which are particularly important to the region. Section four summarizes and takes a look ahead.